The Impact of Early Marriage in Review from the Social, Humanities and Economic Aspects of Farmer Families in Sumbawa Regency: The Impact of Early Marriage in Review from the Social, Humanities and Economic Aspects of Farmer Families in Sumbawa Regency - Noviana, (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
The issue of early marriage is important to note. Based on data from the Sumbawa Regency Religious Court, there are at least more than 20 cases of underage marriages that occurred within two months, namely the January-February 2022 period. Worse yet, most of them are known to be pregnant out of wedlock. The research method is a qualitative method with the aim of digging deeper into information related to early marriage in terms of social, humanities and economic aspects. This research is limited to farmer families in Sumbawa Regency, this is because the average community in Sumbawa Regency has a job as a farmer. The research location was determined by purposive sampling, namely in Labuhan Badas District with the consideration that most of the population still depend on the agricultural sector and cases of early marriage have increased. Data analysis techniques are data reduction, data presentation, conclusion drawing and verification. The results of the study indicate that the low understanding of parents both from the social humanities aspect and the lack of opportunities in the economic field due to the low human resources and the high level of poverty cause early marriages to occur frequently, the impact is the high divorce rate. Mentally they are not ready and economically they are not able.